Implementasi Algoritma Modified K-Nearest Neighbor (MKNN) untuk Klasifikasi Penyakit Demam - Fakihatin Wafiyah; Nurul Hidayat; Rizal Setya Perdana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Fever is an early indicator for some diseases such as dengue fever, typhoid and malaria accompanied by similar symptoms, including muscle pain, indigestion, tongue condition and enlargement of the liver and spleen. Similar symptoms of each disease cause difficulties in getting anamnese (temporary diagnosis) so that patients get the inadequate initial treatment. Handling the problem, technology is needed to obtain a temporary diagnosis by applying one of the classification method of Modified K-Nearest Neighbor (MKNN). The method studied the pattern of previous examination data based on 15 symptoms of disease with eucledian distance calculation process, calculation of validity value and weighted voting calculation that the end result is used for class classification determination based on predetermined value of K. Testing of the value of K get the accuracy of 88.55%. The average value of accuracy obtained from testing of variation in the amount of training data is 92.42%. Testing the influence of the composition of train data get the average value of accuracy of 87.89%. Testing the influence of the composition of train data and test data get the average value of accuracy of 96.35%